1994
DOI: 10.1523/jneurosci.14-06-03655.1994
|View full text |Cite
|
Sign up to set email alerts
|

Central sprouting and functional plasticity of regenerated primary afferents

Abstract: A combination of neuroanatomical and electrophysiological techniques was used to study the effects of peripheral axotomy and regeneration of primary afferents on their central projections in the spinal cord. Individual regenerated afferent fibers were impaled with HRP-filled electrodes in the dorsal columns of alpha-chloralose-anesthetized cats and activated by current pulses delivered via the intracellular electrode. The resulting cord dorsum potentials (CDPs) were recorded at four rostrocaudal locations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
2
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 28 publications
(42 reference statements)
6
101
2
2
Order By: Relevance
“…In addition, other circuits such as GABAergic circuit may also contribute to the gate control, as we have found some GABAergic inhibitory connections in this region. Sprouting of Aβ afferents dorsally into laminae IIo and I, the area that normally receives nociceptive input, was also implicated in nerve injury-induced mechanical allodynia (43)(44)(45)(46)(47), but several latter studies argue against the hypothesis of Aβ afferent sprouting (12,48,49).…”
Section: Figurementioning
confidence: 99%
“…In addition, other circuits such as GABAergic circuit may also contribute to the gate control, as we have found some GABAergic inhibitory connections in this region. Sprouting of Aβ afferents dorsally into laminae IIo and I, the area that normally receives nociceptive input, was also implicated in nerve injury-induced mechanical allodynia (43)(44)(45)(46)(47), but several latter studies argue against the hypothesis of Aβ afferent sprouting (12,48,49).…”
Section: Figurementioning
confidence: 99%
“…Large myelinated mechanoreceptive A␤ fibers normally terminate in lamina III-VI, small myelinated nociceptive A␦ fibers in laminae I and V, and small unmyelinated nociceptive C-fibers in lamina II (substantia gelatinosa) (Brown, 1981;Molander et al, 1984;Molander and Grant, 1985;Willis and Coggeshall, 1991). After injury, however, using B fragment of cholera toxin conjugated to horseradish peroxidase (B-HRP) to selectively label myelinated fibers (Robertson and Grant, 1985;Rivero-Melian and Grant, 1990;Robertson et al, 1991), peripheral axotomy has been shown to cause longlasting sprouting of A-fibers into lamina II, an area in which they do not normally terminate Koerber et al, 1994;Woolf et al, 1995). Intracellular injections have shown that at least some of these fibers are A␤ afferents from lamina III Shortland and Woolf, 1993;Koerber et al, 1994).…”
mentioning
confidence: 99%
“…After injury, however, using B fragment of cholera toxin conjugated to horseradish peroxidase (B-HRP) to selectively label myelinated fibers (Robertson and Grant, 1985;Rivero-Melian and Grant, 1990;Robertson et al, 1991), peripheral axotomy has been shown to cause longlasting sprouting of A-fibers into lamina II, an area in which they do not normally terminate Koerber et al, 1994;Woolf et al, 1995). Intracellular injections have shown that at least some of these fibers are A␤ afferents from lamina III Shortland and Woolf, 1993;Koerber et al, 1994).…”
mentioning
confidence: 99%
“…In addition, peripheral nerve crush or axotomy is associated with synaptic structural plasticity within the neuropil of lamina II. Such plasticity includes synaptic and terminal degeneration of certain C-fiber nociceptive afferents (Knyihar and Csillik, 1976;Kapadia and LaMotte, 1987), as well as sprouting and regeneration of synaptic contacts in which remaining C-fibers or mechanoreceptive A␤-fibers have been implicated (Csillik and Knyihar, 1975;Woolf et al, 1992;Koerber et al, 1994;Kohama et al, 2000). The molecular mechanisms that specify dorsal horn synaptic circuitry and contribute to injuryrelated structural synaptic plasticity and retargeting are mostly unexplored.…”
Section: Introductionmentioning
confidence: 99%